1092. Increased Risk of Serious Infections in Mantle Cell Lymphoma Versus Other Hematologic Malignancies in Patients on Ibrutinib. (31st December 2020) - Holowka, Thomas; Cheung, Harry; Malinis, Maricar F; Perreault, Sarah; Isufi, Iris; Azar, Marwan M
Abstract: Background: Ibrutinib, a tyrosine kinase inhibitor used for treatment of hematologic malignancies, is associated with an increased risk of infection including invasive fungal infections (IFI). However, the risk of infection may vary across different types of malignancies. The primary aims of our study were to determine the incidence of serious infection and associated risk factors in different hematologic malignancies while on ibrutinib. Methods: We performed a retrospective analysis of patients prescribed ibrutinib for ≥ 1 week at Yale New Haven Hospital between January 2014 and July 2019 by chart review. We collected demographic, and clinical data along with oncologic history, and identified serious infections defined as those requiring inpatient management. Chi-squared tests were used to determine characteristics associated with an increased risk of infection. Results: A total of 254 patients on ibrutinib were identified including 156 with CLL, 89 with NHL including 20 with Mantle Cell Lymphoma (MCL) and 9 with other leukemias. Among these, 21 underwent HSCT, 9 complicated by GVHD. Of 51 patients with serious infections, 10 (20%) had MCL, 11 (20.3%) had other NHLs, 28 (54.9%) had CLL and 2 (3.9%) had other malignancies. The relative frequency of serious infections was higher in MCL than non-MCL (50% vs. 17.1%). More MCL patients experienced IFI (1 pulmonary cryptococcosis, 2 pulmonary aspergillosis), compared to non-MCL patients (2 pulmonary aspergillosis; 15% vs. 0.9%). Risk factors associated with serious infection in MCL included maximum ibrutinib dose of 560 mg (OR 16.4, p < 0.001), other concurrent chemotherapy (OR 8.2, p < 0.001), prior HSCT (OR 5.9, p < 0.001), concurrent steroid use (≥ 10 mg prednisone for ≥ 2 weeks; OR 2.4, p < 0.05), lymphopenia (OR 2.4, p < 0.05) a history of prior chemotherapy (OR 0.2, p < 0.05) and ECOG score ≥ 2 (OR 3.2, p < 0.01). Conclusion: In this study of hematologic malignancy on ibrutinib, MCL patients had a greater risk of serious infection. This increased risk in MCL could be associated with more prolonged and intense immunosuppression rather than underlying disease pathogenesis. Antimicrobial prophylaxis should be considered in MCL patients on ibrutinib to mitigate risk of infection. Disclosures: All Authors : No reported disclosures